Analgesic Profile of the Aqueous and Methanol Extracts of Alchornea Laxiflora in Albino Mice - Nwonu, Chukwunwike; Ilesanmi, Olapade; Agbedahunsi, Joseph; Nwonu, Patience (European Scientific Journal, ESJ, 2018)
The study investigated the median lethal dose and the effects of the aqueous and methanol extracts of Alchornea laxiflora in three mouse models of central and peripheral analgesia, the hot plate, acetic acid-induced abdominal writhes and the tail immersion tests. This was with a view to providing information on the acute toxicity, analgesic effects and the possible mechanism of analgesia. The LD50 for the aqueous and methanol extracts of A. laxiflora in the oral route was > 1600 mg/kg respectively, and found to be safe in animals. However, the LD50 (i.p.), was found to be 400 mg/kg for the methanol extract, which was relatively toxic and > 1600 mg/kg for the aqueous extract. Mice of both sexes (n=6) weighing 18 – 22 g were used for the study, which were randomised into control and test, which summed up to eight (VIII) groups. The control group (I) received 10 % Tween 80 (vehicle), 0.1 ml/10 g mouse while the test groups (II,III,IV,V,VI) were administered graded doses (100, 200, 400, 800, 1600 mg/kg, p.o.) of the extracts. The reference groups (VII,VIII) received standard drugs, Acetyl salicylic acid (10 mg/kg, i.p.) and Pethidine (10 mg/kg, i.p.). The animals were observed for their reaction to pain using different noxious stimuli (thermal and chemical). They were appropriately scored individually after observation 30 and 60 min post intraperitoneal and oral administrations of vehicle, extracts or drugs respectively. The results showed that A. laxiflora produced significant (P < 0.05) increase in the mean reaction time to pain in the hot plate and the tail immersion tests. It also produced a significant (P < 0.05) decrease in the number of abdominal writhes. The study concluded that A. laxiflora possesses analgesic activity. The mechanism of the analgesic effect was not through the opioidergic system